ABILITY OF PROSPECTIVE BIOLOGY TEACHER STUDENTS TO COMPOSE HIGHER ORDER THINKING SKILLS (HOTS) TEST ITEMS - Murwitaningsih, Susanti; Mayarni, Mayarni; Sholihah, Chairani; Albantani, Musnika Muharani (Jurnal Biologi Sains dan Kependidikan, 2023)
This study aims to analyze the ability of prospective biology teachers to compose test items that measure students' higher-order thinking skills (HOTS), particularly in the subject of biology. This research employs a qualitative descriptive method. The data source consists of fifth-semester students from the Biology Education Program at Universitas Muhammadiyah Prof. DR. HAMKA during the academic year 2021/2022, who are currently taking the course on Biology Learning Evaluation. Data collection is conducted through documentation techniques and interviews. The data is analyzed by comparing it with the criteria for writing HOTS test items and their alignment with learning outcome indicators. Data validity is tested using triangulation of techniques and sources. The research results indicate that students are capable of composing HOTS items according to the principles, including: measuring high-order thinking abilities, minimizing the recall and understanding aspects by 50.29%; being based on contextual problem-solving by 60.82%; and utilizing engaging stimuli by 48.31%, all of which fall under the 'sufficient' category. Therefore, the average ability of students in composing HOTS test items for the biology subject is 53.14%, categorized as 'sufficient'. The findings of this research are recommended for enhancing students' ability to create HOTS test items and serve as a reference for researchers aiming to improve the quality of teaching, particularly in the Biology Learning Evaluation course."Keywords: HOTS questions, Biology Teacher, Ability, Evaluation, Biology Lessons